From environmental threat to psychological distress: Eco-anxiety as an emerging mental health issue in climate-vulnerable societies - Adhiswar Azizi; Aisyah Ramadhani Anshory (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Climate change has increasingly been recognized not only as an environmental crisis but also as a significant threat to human mental health. One emerging psychological response to this condition is eco-anxiety, which reflects persistent worry, fear, and emotional distress related to environmental degradation and climate uncertainty. In Indonesia, where climate-related disasters and ecological vulnerability are highly prevalent, discussions on eco-anxiety remain fragmented and underexplored within mental health discourse. This study aims to critically review existing literature on eco-anxiety and examine how the climate crisis affects mental health from both global and Indonesian perspectives. Methods: This study employed a qualitative literature review approach by systematically collecting and analyzing scientific publications from national and international databases, including SINTA, Scopus, and PubMed Central. Relevant peer-reviewed journal articles and selected disaster reports were reviewed using thematic analysis to identify key patterns, relationships, and research gaps related to eco-anxiety and mental health. Findings: The review indicates that eco-anxiety is closely associated with psychological distress such as anxiety, stress, and reduced mental well-being, particularly among younger populations and communities exposed to climate risks. Social context, media exposure, and collective experiences were found to intensify eco-anxiety, while adaptive coping mechanisms and social support play important roles in mental resilience. However, empirical research in Indonesia remains limited, with a lack of culturally adaptive measurement tools and integrated policy responses. Conclusion: Eco-anxiety represents a multidimensional mental health challenge that requires greater attention within climate adaptation and public health strategies. Integrating environmental perspectives into mental health services is essential to strengthen psychological resilience amid ongoing climate change. Novelty/Originality of this article: This article contributes a comprehensive and contextualized synthesis of eco-anxiety literature by highlighting research gaps, social dimensions, and policy implications within the Indonesian context, offering an integrative perspective that connects environmental psychology, mental health, and climate change.